Organic deposit remediation using environmentally benign solvents: A review - Elochukwu, O.H. (Asian Research Publishing Network, 2014)
Asphaltene and paraffin wax remains the predominant organic deposit causing depositional problems in the production system. Different methods employed to remedy the problem most times has yielded different results. Chemical approach has proven quite effective due to its near hundred percent resolution of the problem. It is unfortunate that the frequently employed chemical solvents are not environmentally friendly. To this end, green solvent derived from natural and renewable sources are been utilized as an alternative to the conventional solvents for organic deposit remediation. This work critically reviews green solvents: terpene, methyl ester, ethyl lactate and cardanol. These solvents have inherent properties that make them good potential for asphaltene and paraffin wax deposit remediation. A further combination of these green solvent with environmentally friendly surfactants greatly improves their performance to remedy organic deposits. Despite the natural abundance of raw materials for the production of these green solvents, its commercialization and utilization is not wide spread. Â© 2006-2014 Asian Research Publishing Network (ARPN).